Dietary greenhouse gas emissions and resource use among Bavarian adults: associations with sociodemographics and food choices - Gimpfl, Sebastian; Schwarz, Sofia; Rohm, Florian; Ohlhaut, Nadine; Röger, Christine; Senger, Melanie; Kussmann, Martin; Linseisen, Jakob; Gedrich, Kurt (Frontiers in Nutrition, 2025)
BackgroundThis study assessed dietary greenhouse gas emission (GHGE), land use (LU), and water footprint (WFP) among Bavarian residents while exploring sociodemographic characteristics, food consumption patterns, sustainability beliefs, and behaviors across GHGE quintiles.Methods and designThe 3rd Bavarian Food Consumption Survey (BVS III) was conducted from October 2021 to January 2023, involving participants aged 18–75 years. The study employed demographic weighting to represent the Bavarian population. Dietary data (N = 1,100) were linked to sustainability databases.ResultsIn Bavaria, the average dietary GHGE is 6.14 kg CO2eq, with LU at 7.50 m2*yr. and WFP at 4.39 kiloliters per 2,500 kcal. Multivariate regression analyses indicated that females had significantly higher GHGE (β = 0.204, p = 0.023) and WFP (β = 0.466, p < 0.001) compared to males. Waist circumference was positively associated with GHGE (β = 0.011, p < 0.001) and LU (β = 0.035, p < 0.001). Participants following vegetarian or vegan diets show significantly lower GHGE, LU, and WFP than omnivores. High CO2eq emitters also consumed more coffee, tea, and most foods of animal origin. Lowest CO2eq emitters are more inclined to reduce meat consumption (91% vs. 61–77%, p = 0.012), while higher emitters focused on purchasing regional foods (93–95% vs. 80%, p = 0.041).ConclusionThis study provided a view of dietary sustainability metrics in Bavaria. Considering energy-adjusted diets, higher emissions are associated with being female, having a higher waist circumference, and following an omnivorous diet. Increased consumption of animal products, coffee, and tea contributed to greater environmental impacts.